2020
DOI: 10.3390/brainsci10070441
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping without Prescription: Management of Sleep Disorders in Children with Autism with Non-Pharmacological Interventions and Over-the-Counter Treatments

Abstract: Autism Spectrum Disorders (ASD) are lifelong neurodevelopmental conditions characterized by abnormal social interaction, communication, and behavior. Sleep disturbances represent a common comorbidity in children and adolescents with ASD, with prevalence ranging from 50 to 80%. It has been proved that sleep disruption worsens the symptoms of autism and results in challenging behaviors. Improving sleep should therefore be a primary therapeutic goal. Treatment options range from lifestyle modifications to pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 223 publications
2
27
1
Order By: Relevance
“…Sleep disturbances are common in children with ASD [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 21 , 22 ], even if no consensus has been reached about the prevalence of this disorder, probably due to the different tools used as subjective (questionnaires, sleep diaries) or objective assessments (actigraphy, polysomnography) or due to the inclusion of children across wide age ranges. Very few studies have involved young children at pre-school age [ 2 , 5 , 23 , 24 ] or considered the associations between the severity of autism symptoms and sleep problems [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbances are common in children with ASD [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 21 , 22 ], even if no consensus has been reached about the prevalence of this disorder, probably due to the different tools used as subjective (questionnaires, sleep diaries) or objective assessments (actigraphy, polysomnography) or due to the inclusion of children across wide age ranges. Very few studies have involved young children at pre-school age [ 2 , 5 , 23 , 24 ] or considered the associations between the severity of autism symptoms and sleep problems [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the medical conditions known to be associated with ASD, sleep disorders stand out as one of the most commonly reported; their prevalence in ASD children range from 45% up to 86% [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], and they have been shown to have a more chronic nature than those affecting typically developing children [ 6 , 7 ], thus having a significant impact on the health and quality of life of both patients and their caregivers. It has indeed been found that autistic chidren with sleep disorders experience increased daytime symptoms of anxiety, depression, aggressiveness, and attention deficit, as well as greater social impairment and poorer perfomances in cognitive and sensory–motor tasks, compared to autistic children who do not have sleep problems [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the pharmacological treatment of sleep disorders in ASD children has been extensively reviewed, non-pharmacological interventions and nutritional supplements have been relatively under-examined ( 17 ). A separated discussion is required for melatonin, a hormone principally secreted by the pineal gland with an endogenous, circadian rhythm influenced by light/dark conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the “Introduction,” the high prevalence of sleep problems in children with ASD is more likely to be attributed to the pathogenesis of ASD, such as brain wave organizational and maturational differences, arousal and sensory dysregulation, circadian-relevant genes, and abnormal melatonin production ( 28 , 29 ). However, there is no intervention especially for the sleep problems of autistic individuals besides the conventional measures aimed at the behavioral insomnia of children caused by external factors, such as sleep education, sleep environment improvement, behavioral intervention, and drug treatment (such as exogenous melatonin) ( 28 , 30 ). Therefore, the intervention on the sleep problems in autistic individuals should consider the treatment of the core symptoms and sleep problems ( 31 ).…”
Section: Discussionmentioning
confidence: 99%